Habitat use of roe deer in a floodplain forest and the neighbouring agricultural area - Tóth Bálint (Agrár- és vidékfejlesztési szemle, 2011)
The purposes of this study were 1) to determine the annual and seasonal home range sizes of roe deer captured and radio-tagged in a floodplain forest, and 2) to evaluate the habitat-use in light of the differences in vegetation between the floodplain forest and the neighbouring agricultural lands. We used one year localization data of six roe deer equipped with GPS-GSM collars in January 2007. Their home ranges were estimated with minimum convex polygon and kernel home range (with 60% and 90% probability contours) methods. To evaluate the habitat-use we also utilized the land cover map of the study area. The size of the MCP home ranges varied between 500-1000 hectares. The size of the KHRs (90% probability contours) varied between 30-120 hectares, while the core areas (60% probability contours) were between only 5-35 hectares. The core area of each roe deer contained at least 10% forested habitat; while the agricultural habitat type played a significant role only in four of the cases (the proportion of agricultural land was higher than 50% only in three of them). Significant differences were found between home range sizes and also between the proportions of the used habitat types. The results of yearly vegetation-preference calculations showed that each studied roe deer avoided the agricultural lands. Based on these results we suppose that different spaceuse strategies can exist among roe deer living in our study area.